Exploitation of Novel Bt ICPs for the Management of Helicoverpa armigera (Hübner) in Cotton (Gossypium hirsutum L.): A Transgenic Approach - Karthik, Kesiraju; Negi, Jyotsana; Rathinam, Maniraj; Saini, Navinder; Sreevathsa, Rohini (Frontiers in Microbiology, 2021)
Cotton is a commercial crop of global importance. The major threat challenging the productivity in cotton has been the lepidopteron insect pest Helicoverpa armigera or cotton bollworm which voraciously feeds on various plant parts. Biotechnological interventions to manage this herbivore have been a universally inevitable option. The advent of plant genetic engineering and exploitation of Bacillus thuringiensis (Bt) insecticidal crystal proteins (ICPs) marked the beginning plant protection in cotton through transgenic technology. Despite phenomenal success and widespread acceptance, the fear of resistance development in insects has been a perennial concern. To address this issue, alternate strategies like introgression of a combination of cry protein genes and protein-engineered chimeric toxin genes came into practice. The utility of chimeric toxins produced by domain swapping, rearrangement of domains and other strategies aid in toxins emerging with broad spectrum efficacy that facilitate the avoidance of resistance in insects towards Cry toxins. The present study demonstrates the utility of two BtICPs, Cry1AcF (produced by domain swapping) and Cry2Aa (produced by codon modification) in transgenic cotton for the mitigation of H. armigera. Transgenics were developed in cotton cv. Pusa 8-6 by the exploitation of an apical meristem-targeted in planta transformation protocol. Stringent trait efficacy-based selective screening of T1 and T2 generation transgenic plants enabled the identification of plants resistant to H. armigera upon deliberate challenging. Evaluation of shortlisted events in T3 generation identified a total of 9 superior transgenic events with both the genes (6 with cry1AcF and 3 with cry2Aa). The transgenic plants depicted 80-100% larval mortality of H. armigera and 10-30% leaf damage. Molecular characterization of the shortlisted transgenics demonstrated stable integration, inheritance and expression of transgenes. The study is the first of its kind to utilise a non-tissue culture-based transformation strategy for the development of stable transgenics in cotton harbouring two novel genes, cry1AcF and cry2Aa for insect resistance. The identified transgenic events can be potential options towards the exploitation of unique cry genes for the management of the polyphagous insect pest H. armigera.